Ramadan daily intermittent fasting reduces objectively assessed habitual physical activity among adults - Abdualziz Farooq; Karim Chamari; Suzan Sayegh; Maha El Akoum; Abdulla Saeed Al-Mohannadi (BMC, 2021)
Abstract Background Muslims around the world practice intermittent fasting during the month of Ramadan each year. We hypothesized that daily physical activity could be reduced among Muslims due to the inability to refuel and rehydrate in the fasting state. Methods A cohort study design among adults registered with national physical activity community program. Data from a pedometer-based community program was used to extract 3 months of daily step counts before, during, and after Ramadan for the past years (2013-2019). A survey was conducted among participants to determine fasting practice and other health and environmental factors. Results A total of 209 participants completed the survey and provided valid data on physical activity. During Ramadan, the average steps per day decreased significantly (− 385 ± SE 158) among participants who fasted (n = 151) p = 0.046 and increased (+ 731 ± SE 247) for the non- fasting participants (n = 58) p = 0.010. Fasting participants preferred before sunset (33.8%) or evening (39.7%) for physical activity. Whereas, non-fasting participants preferred early morning (34.5%). Conclusion Fasting during Ramadan impacts the daily physical activity behavior among Muslims. Interventions should focus on creating awareness of the importance of maintenance of adequate physical activity for adults fasting during Ramadan.